2011
DOI: 10.1002/bdm.702
|View full text |Cite
|
Sign up to set email alerts
|

Impact of regulatory focus on ambiguity aversion

Abstract: Although prior research has shown that some people prefer a risky to an ambiguous option, this study further proposes that people's regulatory focus (promotion vs. prevention) might influence their ambiguity aversion. Three experiments have tested whether people with promotion focus showed less ambiguity aversion than those with prevention focus: The first experiment revealed that, compared with chronically promotion-focused individuals, prevention-focused subjects preferred a risky to an ambiguous option. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Because promotion‐focused individuals are open to change when faced with decisions (Crowe & Higgins, 1997), they may be more willing to increase allocations to a firm's R&D. They are also more comfortable with ambiguity (Hmieleski & Baron, 2008; Liu, 2011) suggesting that they will be more comfortable investing resources toward initiatives with uncertain outcomes. They may increase R&D spending to try to improve R&D activities, including to produce new innovations, despite the inherent uncertainty.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Because promotion‐focused individuals are open to change when faced with decisions (Crowe & Higgins, 1997), they may be more willing to increase allocations to a firm's R&D. They are also more comfortable with ambiguity (Hmieleski & Baron, 2008; Liu, 2011) suggesting that they will be more comfortable investing resources toward initiatives with uncertain outcomes. They may increase R&D spending to try to improve R&D activities, including to produce new innovations, despite the inherent uncertainty.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Existing studies have found that people's behaviors are affected by the regulatory fit. The regulatory fit will change the individual behaviors, including the risk decision, persuade attention and business decisions [24] [25] [26] Regulatory fit will also make individual generate a sense of right and enhance the individual behavior motivation. It has positive influence on decision-making behavior and products evaluation attitude.…”
Section: Hypothesismentioning
confidence: 99%
“…Participants were asked to rate seven negative emotions (e.g., insecure, scared, and distressed) in enemyship. 2 Some studies suggested that people with different regulatory focus respond differently to the contexts varying in the degree of uncertainty (e.g., Halamish, Liberman, Higgins, & Idson, 2008; Liu, 2011). To explore potential variations across contexts regarding the uncertainty level associated with the enemies, we asked participants to report their emotional experiences in three situations: when they fully understood the current situation of their enemies, when they only had partial information about the current situation of their enemies, and when they had no idea about the current situation of their enemies.…”
Section: Studymentioning
confidence: 99%